HUBUNGAN ANTARA TINGGI BADAN DAN DAYA LEDAK TUNGKAI DENGAN KEMAMPUAN SMASH PADA SISWA SMP NEGERI 2 KOTABARU - Siti Maifa (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2016)
Of the research is descriptive research. This study aims to determine: (1) whether there is a relationship between height with the ability to smash the students of SMP Negeri 2 Kotabaru. (2) whether there is a relationship between the explosive power of the legs with the ability to smash the students of SMP Negeri 2 Kotabaru. (3) whether there is a relationship between height and limb explosive power with the ability to smash the students of SMP Negeri 1 Kotabaru. The population is students of SMP Negeri 1 Kotabaru. The samples used were male students students of SMP Negeri 1 Kotabaru. as many as 30 people. Sampling technique is by random selection by lottery (Simple Random Sampling). Data analysis technique used is descriptive analysis and inferential analysis through SPSS 22 at significant level Î± of 0.05. The results showed that; (1) there is a relationship between height with the ability to smash the students of SMP Negeri 2 Kotabaru, amounting to 0.379. (2) there is a relationship between the explosive power of the legs with the ability to smash the students of SMP Negeri 2 Kotabaru, amounting to 0.641. (3) there is a relationship between height and limb explosive power with the ability to smash the students of SMP Negeri 1 Kotabaru, with a value of F: 9,242 and sig (p) = 0,001.